2015
DOI: 10.1586/14779072.2015.1047763
|View full text |Cite
|
Sign up to set email alerts
|

Approaching atrial septal defects in pulmonary hypertension

Abstract: Atrial septal defects (ASDs) are one of the most frequent congenital cardiac malformations, accounting for about 8-10% of all congenital heart defects. The prevalence of pulmonary arterial hypertension (PAH) in adults with an ASD is 8-10%. Different clinical PAH scenarios can be encountered. At one end of the spectrum are adults with no or only mild pulmonary vascular disease and a large shunt. These are patients who can safely undergo shunt closure. In the elderly, mild residual pulmonary hypertension after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
(31 reference statements)
0
11
0
3
Order By: Relevance
“…Animal models of chronic left-to-right shunting have increased pulmonary vascular resistance and arteriolar medial thickness, implying biologic plausibility to the association between ASD and PH [24, 25]. Epidemiologically, ASDs account for 8–10% of congenital heart defects, though the majority of these close spontaneously in the first year of life [26]. For those with persistent defects, small studies have suggested that infants with BPD may have improved respiratory outcome following transcatheter closure of left-to-right shunts at approximately 6 months of age [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of chronic left-to-right shunting have increased pulmonary vascular resistance and arteriolar medial thickness, implying biologic plausibility to the association between ASD and PH [24, 25]. Epidemiologically, ASDs account for 8–10% of congenital heart defects, though the majority of these close spontaneously in the first year of life [26]. For those with persistent defects, small studies have suggested that infants with BPD may have improved respiratory outcome following transcatheter closure of left-to-right shunts at approximately 6 months of age [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of infants born before 32 weeks' gestation have demonstrated that a higher proportion of infants with PH have ASD, than infants without PH ( 23 ). Although small left-to-right shunts will often close spontaneously after birth, larger and persistent ASDs may ultimately require interventional closure or surgery ( 24 , 25 ). Small studies that have evaluated percutaneous transcatheter device closure of ASD in sick neonates have shown some improvements in respiratory status and medication use post-procedure, suggesting that, in some patients, treatment may improve outcomes ( 17 , 18 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 Shunt reversion in Eisenmenger's syndrome can lead to rightto-left shunt, too, but here the underlying are changes in pulmonary vascular resistance with impaired right ventricular filling and subsequent high right atrial pressures. 15 Persistent hypertension of the newborn can be a potentially fatal course of cyanosis with an isolated atrial septal defect. 16 The mechanism in both these diseases lies in high pulmonary vascular resistance, even if the cause is different.…”
Section: Discussionmentioning
confidence: 99%